Uprising : how women used the US West to win the right to vote - Lewis, Tiffany (Rhetoric and public affairs series., 2021)
"While many scholars have studied why and how the Western states enfranchised women before the Eastern ones, this book instead examines the influence of the West on the US national suffrage movement"--